(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
Pediatric trauma, particularly of mechanical origin, globally, presents a pervasive medical and social challenges. The incidence of such trauma, stemming from various causes including road traffic accidents and other environmental hazards, demands comprehensive investigation to elucidate its etiology, characteristics, clinical manifestations, and preventive strategies.